Curcumin: A Potential Weapon in the Prevention and Treatment of Head and Neck Cancer - Veselá, Kateřina; Kejík, Zdeněk; Masařík, Michal; Babula, Petr; Dytrych, Petr; Martásek, Pavel; Jakubek, Milan (ACS pharmacology & translational science, 2024)
Head and neck cancers (HNC) are aggressive, difficult-to-treat tumors that can be caused by genetic factors but mainly by lifestyle or infection caused by the human papillomavirus. As the sixth most common malignancy, it presents a formidable therapeutic challenge with limited therapeutic modalities. Curcumin, a natural polyphenol, is appearing as a promising multitarget anticancer and antimetastatic agent. Numerous studies have shown that curcumin and its derivatives have the potential to affect signaling pathways (NF-κB, JAK/STAT, and EGFR) and molecular mechanisms that are crucial for the growth and migration of head and neck tumors. Furthermore, its ability to interact with the tumor microenvironment and trigger the immune system may significantly influence the organism's immune response to the tumor. Combining curcumin with conventional therapies such as chemotherapy or radiotherapy may improve the efficacy of treatment and reduce the side effects of treatment, thereby increasing its therapeutic potential. This review is a comprehensive overview that discusses both the benefits and limitations of curcumin and its therapeutic effects in the context of tumor biology, with an emphasis on molecular mechanisms in the context of HNC. This review also includes possibilities to improve the limiting properties of curcumin both in terms of the development of new derivatives, formulations, or combinations with conventional therapies that have potential as a new type of therapy for the treatment of HNC and subsequent use in clinical practice.